Sosialisasi Sistem Informasi Pembelajaran Siswa Slow Learner E-IM3 kepada Guru Pendamping Khusus SMP Negeri Kabupaten Magetan - Anardani, Sri; Murtafiah, Wasilatul; Trisnani, Rischa Pramudia; Putra, Aldeva Rizky Winanto Pratama; Solikah, Nurul Islami; Alifia, Revalina Putri (Pakis Journal Institute, 2025)
The study of inclusive education has been regulated in Law Number 20 of 2023 concerning the National Education System. Based on data obtained from community partnership empowerment activities at Special Assistant Teachers (GPK) of Public Middle Schools in Magetan Regency, it shows that out of 43 GPKs, 86.04% of GPKs have difficulty using discussion and presentation methods in assisting slow learner students in learning mathematics. The problem occurs because there is no media specifically designed by GPK to attract the attention and interest of slow learner students. Following up on this problem, socialization and training activities for the E-IM3 information system were held for 43 GPKs. The activity method was carried out carefully, training in the use of E-IM3, and finally a system evaluation with a User Acceptance Test (UAT). The results of the UAT evaluation showed that the average score of the Software Engineering Test was 4.21, which means that E-IM3 is ready to use. The system functional test had a score of 3.87 and the User Interface (UI) test showed a score of 3.74, which means that there needs to be an improvement in system performance and a more attractive UI design.